MiR-142-5p Acts as a Significant Regulator Through Promoting Proliferation, Invasion, and Migration in Breast Cancer Modulated by Targeting SORBS1. (29th November 2019) - Yu, Weixuan; Li, Dongwei; Zhang, Yunda; Li, Cheukfai; Zhang, Chuanzhao; Wang, Libin
Background: Numerous researches have demonstrated that miR-142-5p plays significant roles in several cancers, although the functional characteristic of miR-142-5p in breast cancer has not been determined. This study is designed to explore the biological significance of miR-142-5p in breast cancer clinical implication and mechanism of action. Methods: The differential expression patterns of miR-142-5p and Sorbin and SH3 domain-containing protein 1 and correlations between them and clinical significances were analyzed based on data from database. The expression levels of miR-142-5p in breast cancer cells were detected using quantitative real-time polymerase chain reaction. Cell counting kit-8, transwell, and wound healing assays were used to explore the potential functions of miR-142-5p in breast cancer cells. In addition, bioinformatics prediction analysis and luciferase reporter assay were utilized to predict and identify the potential target gene of miR-142-5p. A rescue experiment was conducted by transfecting miR-142-5p inhibitors and si-Sorbin and SH3 domain-containing protein 1 into cells to explore miR-142-5p/Sorbin and SH3 domain-containing protein 1 pairs on breast cancer cells behaviors. Results: The analysis results showed that miR-142-5p was highly expressed in patients with breast cancer, while Sorbin and SH3 domain-containing protein 1 presented a trend of low expression. The clinical significances analysis suggested that the overexpression of miR-142-5p is closely correlated with metastasis, while low expression of Sorbin and SH3 domain-containing protein 1 is correlated with clinicopathological characteristics and poor overall survival in patients with breast cancer. In vitro exploration, the expression of miR-142-5p was upregulated in breast cancer cells and inhibition of miR-142-5p expression significantly reduced the proliferation, invasion, and migration of breast cancer cells. Through rescue experiments, breast cancer cells proliferation, invasion, and migration reduction induced by silencing of miR-142-5p were reversed via knockdown Sorbin and SH3 domain-containing protein 1. Conclusion: Our findings insinuate that miR-142-5p functions as a positive regulator of promoting breast cancer cells biological behaviors and clinical metastasis, possibly regulated by targeting Sorbin and SH3 domain-containing protein 1, thus providing valuable information in the development of preventive or even therapeutic strategies for utilizing miR-142-5p as a promising target.